Without Memory? The Conservation of Community Records in the Milanese Contado (14th-15th Centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
At the end of the Middle ages only few of the hundreds of villages that composed the Milanese countryside had their own archives. Local notaries – and not the communities – preserved all public documents which were important for collective life. The essay examines this peculiar situation, arguing for a close connection between record-keeping practices and socio-political balance in the region.DOI 10.17464/9788867743285
Keywords: Archives; rural communities; notaries; Duchy of Milan